Estrategia de marketing de la piladora Yazaida “El Tigre” Del Cantón Pueblo Viejo. - Velásquez Macías, María Mercedes (2022)
By using marketing strategies, this allows improving the profitability levels of the "Piladora Yazaida "El Tigre" del Cantón Pueblo Viejo", by carrying out an adequate analysis about the marketing levels in order to obtain real and updated information as the objective of identifying what is the level of customer satisfaction with the company, allowing the implementation of a marketing strategy that accesses to take advantage of the competitive advantages, managing to increase the profitability of the company, as well as an increase in customer loyalty and how it is must present potential customers giving a better option to choose, it can be based on a problem towards the factors of distribution, marketing and segmentation, which are related to the components of marketing such as the four P's: price, product, promotion, distribution that generates profitability. When promoting marketing strategies to develop commercialization and customer segmentation, it has to be focused on the competitiveness of the company.